PENYUSUNAN ALGORITMA PENDUGA KONSENTRASI Chl-a DAN CITRA KAMERA DIGITAL - Syaiful R. Harahap; Sofyan H. Siregar; Thamrin Thamrin (Jurnal Ilmu Lingkungan, 2007)
The study of assesment model on chl-a was conducted iii Aquaculture pond of Fisheries and Marine Science Faculty, Riau University from May to September 2007. Digital Number (DN) of digital camera and in situ data were used to generate the assesment model using regression analysis. The equation of Chl-a concentration was derived from dig ital camera, i.e. Y= 0.9259X + 0.0024. Y= chl-a concentration and X= (Band 3/(Bandl + Band 2). The formula showed a significant relation between DN of digital camera and Chl-a (r = 0,87) at the level convidence of 95%. The average of C/il-a assesment using the model is 0.25 mg/i. Both of this algorithm was generated to application of hatchery, fish pond and calm waters.